Common beans on-site quality testing tool: Guide for bean practitioners - Espada, Andres David; Reyes, Byron; Colindres, Mirian; Ceballos Sierra, Federico; Irias, Dennis; Salinas, Diana; Wiegel, Jenny (2025)
This innovation manual describes a practical, field-ready system for on-site quality testing of common bean (Phaseolus vulgaris L.) grain. Designed for trained technicians working with farmer associations, NGOs, traders, and research teams, the tool combines a standardized sampling protocol, a KoboCollect XLSForm for offline data capture, and automated calculations to estimate weight discounts and potential income losses. It generates a rapid quality grade from key parameters (moisture, germination, broken or damaged grain, and foreign matter), delivers up to four prioritized, locally appropriate recommendations, and records structured data for monitoring and evaluation. Co-created with farmer associations and piloted in Honduras, the system aims to reduce information asymmetry, help farmers improve post-harvest practices, and support buyers and practitioners in making objective, traceable decisions. This innovation manual is one of two companion documents and must be used together with the XLSForm tool that operationalizes the system.